Self-Supported Smart Bacterial Nanocellulose–Phosphotungstic Acid Nanocomposites for Photochromic Applications - Santos, Moliria V. [UNESP]; Barud, Hernane S.; Alencar, Monica A. S. [UNESP]; Nalin, Marcelo [UNESP]; Toma, Sérgio H.; Araki, Koiti; Benedetti, Assis V. [UNESP]; Maciel, Indhira O.; Fragneaud, Benjamin; Legnani, Cristiano [UNESP]; Molina, Celso; Cremona, Marco; et al. (Frontiers, 2021)
Bacterial nanocellulose (BNC) is a natural biopolymer obtained by gram-negative bacteria by means of a green and inexhaustible biotechnological process using glucose as producing source. BCN hydrogels is formed by cellulose nanofibrils that maintain an open network structure, an ideal matrix to produce new class of organic-inorganic nanocomposites (OIN) for multifunctional applications. The polyoxometalates (POMs) are complex molecules with several metallic ions sharing oxide ions, forming a highly symmetrical metal oxide cluster. Phosphotungstic acid (PWA), H3PW12O40 photoreduction process activated under ultraviolet irradiation, promoting color change. In this work, photochromic organic-inorganic nanocomposites were prepared by soaking phosphotungstic acid (H3PW12O40) in wet BNC membranes mats at room temperature. Semi-transparent and free-standing BNC/PWA nanocomposite with paper-like aspect were obtained. BNC network was able to control, stabilize and disperse PWA particles in a narrow nanometric distribution, and FTIR spectra indicated that the primary Keggin structure was also preserved in the nanocomposites, independently on the PWA content. The nanoparticles present a narrow distribution of around 16 nm, independently on the PWA concentration. BNC/PWA nanocomposites showed reversible photochromic behavior characteristic of the equilibrium between different tungsten oxidation states. PWA reduction (W6+→ W5+) and organic matrix oxidation is proposed to occur through a radical process involving the interaction of one electron from the oxygen atom of the PWA and one hydrogen from BNC matrix. The photochromic effect vanishes almost completely after 5 h. This mechanism is real in the presence of oxygen, however, if the membranes are left in nitrogen or under vacuum the blue color remains longer than 45 days. Photo-electrochemical behavior was studied by spectroelectrochemistry measurements. It is worth noting that all processes were still reversible in the timescale of the experiment and color changes were observed in several cycles.
Keywords: bacterial nanocellulose; electrochromism; phosphotungstic acid; photochromism; polyoxometalates